Major directions in the development of specialized medical aid in the field of dermatovenerology - A. A. Martynov; A. V. Vlasova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article presents the results of a survey of the lines of development for specialized medical aid including high-end one taking into consideration the provisions set out in the Order issued by the President of the Russian Federation under No. 598 "On the improvement of the state policy in the field of health care" on May 7, 2012.